Geotechnical properties of compacted biosolids for monofill design, As-Samra, Jordan - O'Kelly, Brendan (My University, 2020)
This paper presents the results of a comprehensive geotechnical laboratory testing for the assessment and design of a proposed biosolid monofill facility at the As-Samra Waste Water Treatment Plant (WWTP) in Jordan. Previous landfill operations for biosolid materials typically involved co-disposal or lagooning of the dewatered biosolid slurry. However, it is proposed that the solar-dried As-Samra WWTP biosolid material will be placed in a new monofill facility at the site. This approach is suited to the As-Samra desert climate, since the material’s water content can be readily reduced to between 60 and 100% in evaporation lagoons. New insights were gained on the strength and compressibility of the non-inundated and saturated compacted biosolid materials, including their (a) very low normalised undrained strength ratio and effective angle of shearing resistance values for the saturated normally consolidated states of 0·14 and 15°, respectively; (b) very high strain rate dependency of strength; and (c) extremely low permeability coefficient values on the order of 10−12 m/s for compaction at approximately 100% water content. The paper concludes with recommendations on the appropriate water content range for compaction of the material in the proposed monofill and the selection of design strength values for geotechnical stability analysis.
PUBLISHED
Keywords: Biosolids; Monofill; Water content; Jordan; Smart & Sustainable Planet; Environmental Geotechnics; Geotechnical Engineering; Geotechnics; SOIL PARAMETERS; Soil Mechanics; Solid Waste Disposal; Waste Management; Waste Water Treatment